Pemahaman Generasi Z tentang Kafa’ah dalam Pemilihan Pasangan: Analisis Perbandingan antara Praktik Sosial dan Ajaran Hadis - Annisa Dwi Ramadhanti; Nasrulloh (Al-Kindi, 2026)
This study explores how Generation Z understands the Islamic concept of kafa’ah in partner selection and compares their perceptions with normative principles derived from prophetic traditions. Using a mixed-methods approach, the research integrates quantitative survey data from respondents aged 18–25 with qualitative analysis of relevant hadiths and classical as well as contemporary fiqh interpretations. The findings reveal that Generation Z holds diverse and often fragmented interpretations of kafa’ah, ranging from religious–moral compatibility to socio-economic and personal suitability, while a portion of respondents lack familiarity with the concept. Although most participants perceive the hadith principles on kafa’ah as still relevant, their partner selection practices are more strongly shaped by emotional compatibility, lifestyle preferences, and digital cultural influences. A notable gap emerges between normative Islamic teachings and the lived relational practices of contemporary youth. The study concludes that kafa’ah requires contextual reinterpretation to remain applicable within the social and psychological realities of Generation Z.